IMPLEMENTASI KEBIJAKAN PENEMPATAN POS-POS BADAN PENANGGULANGAN BENCANA DAN PEMADAM KEBAKARAN KOTA PALEMBANG - Citra Iasha (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2020)
The background of the problem of high fire frequency from year to year in the Palembang City area shows that the fire prevention efforts carried out by the Palembang City Fire Department organization. In South Sumatra there are many strategic places for various sector centers to support the provincial capital. For example, the center of the economy, business, entertainment, education, and the government of Jakarta as the center of the country and the density of settlements so that there is often a fire hazard. The purpose of this research is to find out how the implementation of the policy of placing the posts of disaster management agencies and firefighters in Palembang city. This research is a qualitative study using data collection methods in the form of interviews with predetermined sources. The results of this study are based on observations and interviews by the author that the implementation of policies carried out by the disaster management agency and the Palembang city fire department has gone well, this is based on the results of interviews using indicators put forward by almost all informants saying it is quite good and already good. This means that the implementation of policies for aligning disaster management and fire fighting agency posts has been good.